(3fgGjI GdWdH aj TQM GdecJSH aj RQGYI GdPgHs - (3Ydj Hf eMeO Hf CjOeQ GdLdOcqj , YR GdOjf J (B742 (3g` s; (3CHh GdbGSe eMeO Hf CMeO GdSjeGhj GdYQGbjs
(3ChdgG (B:s
(3GdMeO ddg GdPi JYGdi Yf GdYdd hGdeYhdGJ s
(3BNQgG (B:s
(3aGage eG GTQfGg Gdjc hGTcQ Gddg Ydi fYeJg Jcf ef GdaGFRjf hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs